Influence of Felling Season and Moon Phase on Natural Resistance of Bamboos against Termite - Dhawan, Seema; Mishra, S. C. (Indian Forester, 2005)
Bamboos form an integral part of rural and urban life style. It has over 1500 uses and tremendous versatility in many aspects of daily life. In ground contact it has only one to two years’ service life as it is usually affected by termites. Knowing the rising cost of repairs a study of natural termite resistance of bamboo becomes very relevant and important. The three bamboo species studied were B. polymorpha, B. aundinacea and D. stricuts for their natural resistance abgainst termite M. beesoni Snyder under laboratory conditions. These were found significantly different in their natural resistance and D. strictus is found as the most resistant species and B. arundinacea is the least among the species studied. Season has the great influence on the durability of bamboo species. The bamboos harvested during winter months were more resistant to termite attack than harvested during summer. Effect of the Moon phase is found significant on termite resistance. The bamboos felled during dark phase were comparatively more resistant than felled in moon phase. These findings could be effectively used for harvesting of bamboos and selection of suitable species along with the season. However, more studies are required to confirm the tests.